The Mental Well-Being of Italian Adolescents in the Last Decade through the Lens of the Dual Factor Model - Bersia, Michela; Charrier, Lorena; Berchialla, Paola; Cosma, Alina; Comoretto, Rosanna Irene; Dalmasso, Paola (Children (Basel, Switzerland), 2022)
(1) Background: In Italy, the components of adolescents' mental well-being (psychological symptomatology and cognitive perception of life satisfaction) showed different temporal trends, suggesting the adoption of a multidimensional conceptualization. We aimed to assess temporal patterns and provide additional insights into Italian adolescents' mental well-being in the last decade by adopting the Dual Factor Model; (2) Methods: We used nationally representative samples of Italian students (n = 165,000) aged 11, 13, and 15 years across the three more recent Italian Health Behaviour in School-aged Children (HBSC) surveys. Two measures of mental well-being were used: life satisfaction (LS, indicator of positive subjective well-being) and psychological health complaints (PHC, indicator of mental illness); (3) Results: Our study showed that the overall sample has been moving from a Complete Mental Health (Flourishing) to an Incomplete Mental Illness (Struggling) condition. Among 13- and 15-year-old girls, a jump from one to the other mental condition was observed in the 2014-2018 and 2010-2014 time periods, respectively; (4) Conclusions: Our findings suggest that Italian adolescents, especially older girls, have been shifting from Complete Mental Health to Incomplete Mental Illness in the last decade. Further research is needed to investigate this breaking up of the connection between psychological symptomatology and cognitive perception of life satisfaction.
Keywords: Dual Factor Model; gender; adolescents; mental well-being; psychological symptoms; HBSC; life satisfaction; mental health